2022
DOI: 10.1097/cm9.0000000000002323
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic analysis of skin keratinocytes in patients with type 2 diabetes based on the single-cell levels

Abstract: Background: Keratinocytes play an important role in wound healing; however, less is known about skin keratinocytes in patients with type 2 diabetes mellitus (T2DM). Therefore, this study aimed to search for the transcriptional characteristics of keratinocytes at the single-cell level from T2DM patients, and to provide experimental data for identifying the pathological mechanisms of keratinocytes under pathological conditions. Methods: We performed single-cell RNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Collagen fi-bres are thick, long and with sinuous tracts, forming a dense, semi-coordinated connective tissue (Figure 7). In the presence of chronic hyperglycaemia, free glucose molecules spon-taneously attach to protein molecules in a process of non-enzymatic glycosylation, which has also been shown in other proteins, which leads to morphological and molecular changes that significantly influence some physical properties, such as flexibility [6][7][8][9]24].Early characterization and quantification of the pathophysiological details of diabetes mellitus and its complications correlates with more effective diagnostic and therapeutic methods, and implicitly with improved survival and quality of life [23,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen fi-bres are thick, long and with sinuous tracts, forming a dense, semi-coordinated connective tissue (Figure 7). In the presence of chronic hyperglycaemia, free glucose molecules spon-taneously attach to protein molecules in a process of non-enzymatic glycosylation, which has also been shown in other proteins, which leads to morphological and molecular changes that significantly influence some physical properties, such as flexibility [6][7][8][9]24].Early characterization and quantification of the pathophysiological details of diabetes mellitus and its complications correlates with more effective diagnostic and therapeutic methods, and implicitly with improved survival and quality of life [23,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the proportion of M1 macrophages (classically activated macrophages that promote inflammation) was higher in DFU-healer than in DFU-non-healers, compared to that of M2 macrophages (alternatively activated macrophages with anti-inflammatory properties)[ 9 ].These results implied that suppressing systemic immuno-inflammatory responses while activating local responses in the wound environment could facilitate diabetic wound healing. Liao et al [ 10 ] found highly expressed keratinocyte genes in the diabetic wound, including SFN, LYPD3, S100A8, KRT1, KRT10, KRT6A, KRT5, and KRT16, underscoring the crucial role of keratinocytes in diabetic wound healing. By analysing the skin specimens of DFU patients and healthy controls using scRNAseq, Du et al [ 11 ] found that human dermal microvascular endothelial cells (HDMECs) isolated from DFU patients showed considerably impaired tube formation compared to those from healthy controls; they also found that the significantly under-expressed RAB17 in DFU-HDMECs may be the key factor leading to the impaired angiogenic capacity in DFUs.…”
Section: Single-cell Sequencing In Diabetic Wound Healingmentioning
confidence: 99%
“…The differential gene expression revealed by scRNAseq also suggested the activation or inhibition of the corresponding signalling pathway in the process of diabetic wound healing. The diabetic healing-related differentially expressed gene analysis and gene ontology functional enrichment analysis identified significant differential genes, including CD19, Integrin Subunit Alpha M, HLA-DR, CXC chemokine ligand 11, MMP1, heparan sulfate 3-O-sulfotransferase 2, CALML, interleukin (IL)7R, IL6, TCF7, CCR7, IL1B, S100A8, HIF1α, TNF, CD44, transforming growth factor β1, C-C chemokine ligand 5, SOX4, RAB17, CD200 and vascular endothelial growth factor A[ 7 , 10 ]. These genes were predominantly associated with the immune and inflammatory signalling pathways, oxidative phosphorylation and cytokine receptor interactions, suggesting that the immune and inflammatory environment is critical for diabetic wound healing.…”
Section: Single-cell Sequencing In Diabetic Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation